Generalized cyclic bond-slip model of rebar embedded in concrete under lateral pressure: Parameter calibration and numerical implementation. (March 2023) - Zhang, Xue; Zhao, Yuheng; Zhao, Ailin; Li, Xinxin
Abstract: For some reinforced concrete members, the bond-slip between rebar and concrete is sometimes affected by the lateral pressure, e.g., the beam-column joint with the axial load induced by the column. For such cases, a cyclic bond-slip behavior taking into account the effect of lateral pressure is of great significance for seismic numerical analysis of these members/structures. So far, however, there is no available numerical approaches which can consider the cyclic bond-slip behavior of RC member under lateral pressure. Therefore, this study presents a generalized bond-slip model, which can consider the effect of cyclic loads and lateral pressure simultaneously. Based on the existing test data, the key parameters of the model are calibrated, so that the model can be used for arbitrary cyclic loading history and is easy to be implemented into existing displacement-based numerical code. Furthermore, a four-node zero-thickness bond element is developed in commercial software ABAQUS. The proposed model is implemented into the bond element and verified by the experimental results. The bond element is preliminarily applied to the force–displacement analysis of reinforcing bars in the beam-column joint, and the feasibility of the model in member-level analysis is discussed based on the numerical results.